The Impact of Implementation of STEAM Project on Mathematics Classroom Learning Environment - Nurwati Djam'an; Suradi Tahmir (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2024)
This study aims to describe the students' perception of their mathematics classroom learning environments in class VIII of SMP IT Ar-Rahmah after implementing the STEAM Project. The type of research is a mixed method. Data were collected using questionnaires and interviews. Based on the results of data analysis, the following conclusions were drawn: (1) the student mathematics learning outcomes are in the high category; (2) The perceptions of the learning environment indicate that the post-test scores were slightly higher than the pre-test scores for all scales: Student Cohesiveness, Teacher Support, Involvement, Investigation, Task Orientation, Cooperation, Equity;  (3) The teacher prepared the project design in teaching the 3D shape, students also have to work in groups, communicate,  presenting their work, and all the students had the opportunity to engage with mathematical content.